(untitled) (Research, Society and Development, 2022)
In the context of Human Resources, one of the most relevant practices for the success of companies concerns the planning, execution and evaluation of training. In addition to being a way to prepare employees to take on new roles, training can be seen as necessary actions to enhance human capital in organizations. The present study aims to highlight the relevance of training practices to boost sales in a cosmetics company in the South of Brazil. The study was developed in a company located in the state of Paraná. It consists of an exploratory study, which generated qualitative data with the research participants through the application of a questionnaire. The results showed that the aforementioned company is well evaluated by customers in relation to its products, with purchases of at least 2 items per month. Another point that was well evaluated concerns the knowledge of sellers about the products offered to customers. However, points for improvement were also detected, such as the presentation of salespeople, which is not always congruent with the principles of personal marketing, as well as delays in the delivery of products to customers. The study concluded that although the company here called Cosmeticos has strengths in its area of operation, which was highlighted through a SWOT analysis, it is necessary to work on points of improvement so that its service is recognized as of quality by your customers.